The transformation of mental health student nurse attitudes during their pre-registration course - Maplethorpe, Fran (2018)
The nurse/patient relationship is seen as central to the heart of mental health nursing and in this thesis I examine how student nurses perceive the concept of therapeutic in regards to these relationships. Contemporary treatment of mental illness is largely based on what are known as ‘recovery’ principles, which emphasise patients’ capacity to regain mental health. This approach is contrasted to forms of treatment and caring underpinned by such attitudes as ‘authoritarian’, ‘benevolent’ or ‘restrictive’ which assume that patients are essentially different from the healthy norm. Recovery principles are embedded in most pre-registration curricula for mental health nurses which aims to develop knowledge about and attitudes congruent with recovery attitudes. While policy and nurse education promote recovery principles, the attitudes of the general public lag behind, tending to ‘other’ people with mental illnesses. The issue this thesis addresses is that mental health student nurses begin their courses with attitudes aligned to those of the general public. There has to date been no investigation into whether their educational experiences change their attitudes to a recovery one. The research was a longitudinal, in-depth case study of a cohort of six mental health nurse students as they progressed through the three years of their pre-registration course (2011-2014). Mixed methods were used to address the research question: Does mental health nurse education promote transformative learning which values and respects the diversity of individuals and enables their recovery, if so how and if not why not? First their attitudes were assessed at the beginning of the course by using the Attitudes to Mental Illness Questionnaire (AMIQ) and then repeated towards the end of the course to compare responses. Four other methods for generating data throughout the course indicated what factors influenced attitudinal change: audio-recorded classroom discussions, recovery assignments, individual semi-structured interviews; and a discussion with the six students about their pictorial representation of their educational experience. Thematic framework analysis was employed drawing on Mezirow (2009) theory of transformative learning and Burnard’s (1987) typology of nursing knowledge to explore whether and how different types of knowledges bring about transformation in attitudes. From a ‘benevolent’ attitude when commencing the education, all the students made marked movements towards a ‘recovery’ one. With one exception, the students went through the transformative phases of learning towards taking on recovery principles, although not all went through all the phases and not all fully incorporated recovery principles into their practice. It is argued that transformative learning is a complex slow process and that it took all forms of knowledge and the full three years for the students to take up attitudes which underpin the recovery principles. The implications and suggestions for mental health nurse education, policy and practice are explored in light of the findings. Moreover, I argue that, all nurse education should include some knowledge about values of care and different theories of mental illness. If the transformational process is to be smooth consideration should be given to the sequencing of different types of knowledge into the curriculum.